Drumlins Of The Puget Lowland, Washington State, Usa - Goldstein, Barry S. (Sedimentary Geology, 1994)
The last advance of the Puget Lobe, a piedmont glacier that extended southward down the axis of the fjord-like Puget Lowland from the main mass of the Cordilleran Ice Sheet, produced an extensive drumlin field approximately 170 km in length and nearly 100 km wide. The timing of both the advance and retreat of the lobe across the region is well constrained, and took no more than a total of 1500 years. In the southern portion of the field, drumlin axis orientations are more closely perpendicular to recessional ice margin positions than to the reconstructed ice-maximum surface contours. This suggests that the drumlin field was formed in a time-transgressive manner as the ice front retreated from south to north, and that each of the numerous recessional phases was characterised by a narrow drumlin-forming zone that extended no more than a few kilometres back from the margin. This would also indicate that only a few decades were required for the formation of individual drumlins in the Puget Lowland. The drumlin forms are composed of compact till that overlies and truncates a 100 m thick sand and gravel unit. The sand has been interpreted as proglacial outwash, originally formed as a continuous blanket deposited in front (south) of the advancing Puget Lobe. It forms the main component within the lower 10-50% of the drumlin till, while farther-travelled components appear in progressively greater proportion with increasing height above the contact. The drumlins are thus interpreted as being of constructional origin. Evidence of minor subglacial meltwater activity occurs in the form of scattered, discontinuous water-sorted lenses interbedded throughout the till. The entire drumlin field is subdivided into a series of sub-parallel regions separated by deep troughs that extend to depths as great as 850 m below the drumlin-capped upland surface. Regional relationships indicate that the drumlins and the troughs formed contemporaneously, but that both post-date the deposition of the outwash. Thus, drumlin formation (net ...